Livelihood Activities and Food Security Status of Households in Oyo Town, Oyo State - Adebimpe, Oke Margaret; Oyebola, Ogundokun Esther; John, Odozie (ESUT JOURNAL OF SOCIAL SCIENCES, 2022)
Previous studies in Nigeria focused on food security and livelihood activities of households using uni-dimensional measures. This paper considered Dietary Diversity Score, Food Consumption Score and food Insecurity Access Scale as measures of the food security status of households. This study aimed at ascertaining the effect of livelihood activities on food security of household’s in Atiba Local Government Area. The study used purposive sampling technique to select 6 wards making up Oyo town upon which in the second stage a random sampling of 114 households were selected. Questionnaires were used to source information on food item consumed, livelihood activities and livelihood assessment. Data were analyzed using the descriptive statistics and logit regression. The result showed that 62% of the respondents were male and 38% were female. 80% fall between the age range of 31-64 years, 60% were married and 61% have a household size ranging between 5 and 8 members. The findings also showed that 58.41% are food secure using Household Dietary Diversity Score, 46.90% using Food Consumption Score, while 55.75 are less food secure using Household Dietary Diversity Score and Sustainable Livelihood Framework Condition respectively. Respondents from Ajayi Crowther University Community, Atiba, Oriawo and Tokun Village are food secure using two measures. The logit regression result confirms that food security increases as trading, private paid job, civil service, and casual job as a means of livelihood were significant while food security decreases with increase in household size at five percent for Household Dietary Diversity Score and Food Consumption Score. The logit value (72.74) indicated relationship between the combined effect of livelihood activities and food security. Food security in Atiba Local Government was low, the respondents’ livelihood activities should be diversified to be more food secured.